Sustainable Islamic Development Management Based on Maqashid Syariah - Sulthon Elhasbi Rambe; Baleo Hilal Hasibuan; Imam Haryadi; Soritua Ahmad Ramdani Harahap; Muhammad Qodri Pangestu (Islamic Business and Management Journal, 2023)
The role of Islamic millennial development has a very positive impact on the progress of the nation. Starting many groups on behalf of the hijrah community, da'wah is filled by young people. This research method uses the literature review method by reading primary and secondary literature on development and maqashid sharia. This shows that young people are not negligent with this challenging life. This article aims to find out how maqashid sharia views on sustainable Islamic development. The results of this study explain that the concept of maqasid al-syari'ah is essentially based on revelation to realize the benefits of human life. Considering that maqasid al-syari'ah formulated by scholars rests on five basic needs (benefits) of human life: maintenance of religion, soul, mind, offspring, and property in accordance with the context of the times, a discourse emerged to develop the concept of maqasid al-syari'ah by adding five basic human needs in accordance with the conditions of modern times.